2010
DOI: 10.4067/s0034-98872010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Leisure time behaviors: Prevalence, correlates and associations with overweight in Brazilian adults. A cross-sectional analysis

Abstract: Background: Television viewing (TV viewing) is an important indicator of phy (Rev Med Chile 2010; 138: 29-35).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
8

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
0
10
0
8
Order By: Relevance
“…In a longitudinal study performed by Zuo et al 19 in China, it was verified, in a sample of 1,224 adults, that the practice of physical activities was pointed out as a prevention factor against sleep disorders. On the other hand, the insufficient practice of physical activities did not remain associated to the outcome after the addition of the excess of weight (overweight and obesity), showing that this possible protective effect of physical activities, apparently, is due to the lower BMI of the subject, i.e., more active people have better quality of sleep because they have lower adiposity levels 32 . Women presented higher occurrence of sleep disorders.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a longitudinal study performed by Zuo et al 19 in China, it was verified, in a sample of 1,224 adults, that the practice of physical activities was pointed out as a prevention factor against sleep disorders. On the other hand, the insufficient practice of physical activities did not remain associated to the outcome after the addition of the excess of weight (overweight and obesity), showing that this possible protective effect of physical activities, apparently, is due to the lower BMI of the subject, i.e., more active people have better quality of sleep because they have lower adiposity levels 32 . Women presented higher occurrence of sleep disorders.…”
Section: Discussionmentioning
confidence: 96%
“…This association shows that factors related to school education (economic condition and occupation) may interfere in the processes related to sleep disorders. The school education has been used as an economic status indicator 27,28,32 , and lower school education refers back to more stressful occupations as well as to lower access to health services with the intention of prevention 35 . Also, higher school education may also mean higher capability of association of what are beneficial health behaviors and, thus, preventing problems which may cause sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have indicated that the practice of physical exercise in childhood and adolescence, more than those practiced in adulthood, is an important determinant in the occurrence of outcomes such as hypertension, type 2 diabetes mellitus and dyslipidemia at adult age 7,8 . However, in these studies, physical exercise in adulthood and that performed during childhood and adolescence were treated as independent variables and, thus, did not clearly assess the true importance of the continued practice of physical activity throughout life over these diseases.…”
Section: Introductionmentioning
confidence: 99%
“…No entanto, a avaliação do NAF é complexa, porque esse é um comportamento multidimensional, que ocorre em vários domínios, tais como transporte, atividades domésticas, lazer, trabalho (adultos) ou escola (crianças e adolescentes), e é provável que cada domínio precise ser avaliado separadamente, não apenas porque essa abordagem torna a informação mais específica, mas também porque é mais provável que a informação seja válida 3 . Além disso, domínios de atividade física diferentes podem estar associados, de diversas formas, ao mesmo desfecho em saúde 4,5 .…”
Section: Introductionunclassified